The effect of intellectual capital, dividend policy, and capital structure on financial performance (Study in food and beverage subsector listed on the Indonesia Stock Exchange 2010-2020 period) - Ayu Mona Rasuani; Mahatma Kufepaksi (Lighthouse Publishing, 2022)
This study aims to determine the effect of intellectual capital with components consisting of VACA, VAHU and STVA, dividend policy and capital structure on financial performance. In the era of industrial globalization, the company's ability to become a benchmark to describe the company's financial condition. The importance of financial performance is to see how the company achieves its goals to gain profits and prosper the company's economy. Based on the results of previous studies, there are inconsistencies in proving variables that can affect financial performance. This study uses secondary data from the food and beverage sub-sector population listed on the IDX for 2010-2020. The method used in this study uses purposive sampling and multiple linear regression models to test the effect of the independent variable on the dependent variable. Based on the research results, the independent variables that significantly positively affect financial performance are STVA (Structural Capital Value Added) and DPR (Dividend Payout Ratio). In contrast, the variable that has a significant but negative or opposite effect is LDER (Long Debt Equity Ratio). Variables VACA (Value Added Capital Employed) and VAHU (Value Added Human Capital) do not affect financial performance. This study suggests using a broader object and not only focusing on the food and beverages subsector.